The influence of renal dialysis and hip fracture sites on the 10-year mortality of elderly hip fracture patients: A nationwide population-based observational study. Issue 37 (September 2017) - Hung, Li-Wei; Hwang, Yi-Ting; Huang, Guey-Shiun; Liang, Cheng-Chih; Lin, Jinn
Abstract : Abstract: Hip fractures in older people requiring dialysis are associated with high mortality. Our study primarily aimed to evaluate the specific burden of dialysis on the mortality rate following hip fracture. The secondary aim was to clarify the effect of the fracture site on mortality. A retrospective cohort study was conducted using Taiwan's National Health Insurance Research Database to analyze nationwide health data regarding dialysis and non-dialysis patients ≥65 years who sustained a first fragility-related hip fracture during the period from 2001 to 2005. Each dialysis hip fracture patient was age- and sex-matched to 5 non-dialysis hip fracture patients to construct the matched cohort. Survival status of patients was followed-up until death or the end of 2011. Survival analyses using multivariate Cox proportional hazards models and the Kaplan-Meier estimator were performed to compare between-group survival and impact of hip fracture sites on mortality. A total of 61, 346 hip fracture patients were included nationwide. Among them, 997 dialysis hip fracture patients were identified and matched to 4985 non-dialysis hip fracture patients. Mortality events were 155, 188, 464, and 103 in the dialysis group, and 314, 382, 1505, and 284 in the non-dialysis group, with adjusted hazard ratios (associated 95% confidence intervals) of 2.58 (2.13–3.13), 2.95 (2.48–3.51), 2.84 (2.55–3.15), and 2.39 (1.94–2.93) at 0 to 3 months, 3 months to 1 year, 1 to 6 years, and 6 to 10 years after the fracture, respectively. In the non-dialysis group, survival was consistently better for patients who sustained femoral neck fractures compared to trochanteric fractures (0–10 years' log-rank test, P  < .001). In the dialysis group, survival of patients with femoral neck fractures was better than that of patients with trochanteric fractures only within the first 6 years post-fracture (0–6 years' log-rank, P  < .001). Dialysis was a significant risk factor of mortality in geriatric hip fracture patients. Survival outcome was better for non-dialysis patients with femoral neck fractures compared to those with trochanteric fractures throughout 10 years. However, the survival advantage of femoral neck fractures was limited to the first 6 years postinjury among dialysis patients.